MACBA : El museu pren forma : Memòria d'actvitats 1995-1996 (any inaugural). - Bosch, Eulàlia; Combalía, Victoria; Juncosa, Enrique; Maragall, Pasqual; Molins i Nubiola, Miquel; Perelló, Antonia Maria; Picazo, Glòria; Pujol, Jordi; Riley, Terence; Rodés, Leopoldo; Sardà, Zeneida; Uslé, Juan; et al. (Barcelona : MACBA (Museu d'Art Contemporani de Barcelona), 1996)
Rauschenberg, Robert ; Sicilia, José Maria ; Ràfols Casamada, Albert ; Fontana, Lucio ; Dubuffet, Jean ; Broto, José Manuel ; Tàpies, Antoni ; Klee, Paul ; Solano, Susana ; Boltanski, Christian ; Barcelo, Miquel ; Tàpies, Antoni ; Pistoletto, Michelangelo ; Kiefer, Anselm ; Navarro, Miquel ; Calder, Alexander ; Guinovart, Josep ; Oteiza, Jorge ; Ponç, Jean ; Long, Richard ; Brossa, Joan ; Millarès, Manuel ; Basquiat, Jean Michel ; García Sevilla, Ferran ; Zush ; Hernandez Pijuan, Juan ; Uslé, Juan ; Sterbak, Jana ; Perejaume ; Oursler, Tony ; Trockel, Rosemarie ; Palazuelo, Pablo ; Armajani, Siah ; Kurgan, Laura ; Rousse, Georges ; Kandinsky, Wassily ; Balcells, Eugènia
Catalaans & Engels & Spaans
boek
Keywords: Barcelona; Spanje